Short-term UV-B radiation effects on morphology, physiological traits and accumulation of bioactive compounds in Prunella vulgaris L. Issue 1 (1st January 2017) - Zhang, Xue-Rong; Chen, Yu-Hang; Guo, Qiao-Sheng; Wang, Wen-Ming; Liu, Li; Fan, Jin; Cao, Li-Ping; Li, Chen
ABSTRACT: Prunella vulgaris plants (full-bloom stage) were subjected to short-term (15 days) UV-B radiation in a growth chamber. UV-B radiation was effective at enhancing morphological and biomass characteristics and decreasing chlorophyll contents of P. vulgaris . Treatment of P. vulgaris with artificial UV-B radiation significantly increased peroxidase (POD), superoxide dismutase (SOD) and glutathione (GSH) activities compared to the control treatment. UV-B radiation significantly increased the levels of hydrogen peroxide (H2 O2 ), malondialdehyde (MDA) and proline in leaves of P. vulgaris compared to those of control plants. In addition, the contents of total flavonoids, rosmarinic acid, caffeic acid and hyperoside significantly increased under UV-B radiation. The total phenolic levels also increased under UV-B treatment. These results demonstrated that short-term UV-B radiation can enhance production of secondary metabolites in P. vulgaris, resulting in increased spica yield compared to that of control plants.